Current view on retinal OCT imaging nomenclature and terminology - N.S. Lutsenko; O.A. Rudycheva; O.A. Isakova; T.S. Kyrylova (Ukrainian Society of Ophthalmologists, 2020)
Optical coherence tomography (OCT) is an essential non-invasive and non-contact diagnostic modality in ophthalmology which allows detailed visualization of posterior segment structures. There have been numerous publications on OCT imaging terminology and OCT-based identification and discrimination of retinal and choroidal structures. Variability in the views of authors and researchers on retinal layer structure as seen on OCT resulted in changes in the nomenclature over the years. The purpose of this review was to generalize and systematize the existing terms constituting an OCT lexicon and relevant to identification of the posterior segment structure and description of structural changes. Knowledge of the nomenclature for OCT and relevant terminology will be essential for experience sharing among ophthalmologists and enable better understanding of pathological retinal and choroidal changes, resulting in improved quality of OCT diagnostic studies.